Percepatan Penyertipikatan Tanah melalui Kebijakan Pendaftaran Tanah Sistematis Lengkap di BPN Provinsi Lampung - Rusli, Tami; Aprinisa, Aprinisa; Elvionita, Maulia (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2023)
Land as a part of life and as a foothold for humans on earth has an important role as a source of welfare, prosperity, and life. Land registration in Indonesia has been regulated in Article 19 of Law Number 5 of 1960, then implemented by Government Regulation Number 10 of 1961 which has been in force for 27 years, then replaced by Government Regulation Number 24 of 1997 which has come into force since October 8, 1997. This article discusses the implementation of a complete systematic land registration policy for obtaining accelerated land certificates at the National Land Agency of Lampung Province. The research method used is normative-juridical research. The approach used by the author is the statutory approach. The results of the research discussion show that land registration determines the legal relationship between people and land as fixed objects. The legal relationship between people and land as a fixed object is included in land law and is not part of agrarian law. A collection of laws governing the synergistic relationship of various branches of law and the legal status of civil rights of people over land as permanent objects, which are controlled to be owned and used and enjoyed by humans, both individually and in the form of communities living together. ___ Referensi Buku dengan penulis: Arifin, F. S. (2008). Pembaruan Agraria Nasional (PAN) dengan Program Sertipikasi Tanah melalui Prona guna Menyukseskan Tertib Administrasi Pertanahan di Kabupaten Pemalang. Semarang: Program Pasca Sarjana Universitas Diponegoro. Artikel jurnal: Ardani, M. N. (2019). Tantangan pelaksanaan kegiatan Pendaftaran Tanah Sistematis Lengkap dalam Rangka Mewujudkan Pemberian Kepastian Hukum. Gema Keadilan, 6(3), 268-286. Ayu, I. K. (2019). Problematika Pelaksanaan Pendaftaran Tanah melalui Pendaftaran Tanah Sistematis Lengkap di Kota Batu. Legality: Jurnal Ilmiah Hukum, 27(1), 27-40. Binter, A., Hermawan, D., dan Yulianti, D. (2019). Implementasi Program Pendaftaran Tanah Sistematis Lengkap di Kecamatan Bangun Rejo Kabupaten Lampung Tengah. Jurnal Administrativa, 1(1), 55-62. Elisa, N. (2022). Sosialisasi Kepastian Hak Atas Tanah melalui Pendaftaran Tanah Sistematis Lengkap (PTSL) di Kabupaten Deli Serdang. Jurnal Pengabdian Kontribusi, 2(1), 45-50. Lika, S. D. R., dan Sholichah, N. (2020). Implementasi Kebijakan PTSL (Pendaftaran Tanah Sistematis Lengkap) di Desa Medaeng Kecamatan Waru Kabupaten Sidoarjo. Journal of Social Politics and Governance (JSPG), 2(1), 63-72. Marryanti, S., dan Purbawa, Y. (2018). Optimalisasi Faktor–Faktor yang Mempengaruhi Keberhasilan Pendaftaran Tanah Sistematis Lengkap. BHUMI: Jurnal Agraria dan Pertanahan, 4(2), 190-207. Masnah, M. (2021). Implementasi Kebijakan Pendaftaran Tanah Sistematis Lengkap (PTSL) di Kabupaten Muaro Jambi. Jurnal Renaissance, 6(2), 783-801. Mujiburohman, D. A. (2018). Potensi Permasalahan Pendaftaran Tanah Sistematik Lengkap (PTSL). BHUMI: Jurnal Agraria dan Pertanahan, 4(1), 88-101. Panjaitan, B., Siregar, R., dan Jannah, M. (2022). Analisis Yuridis Proses Pendaftaran Tanah Sistematis Lengkap (PTSL) Berdasarkan Surat Keputusan Bersama 3 Menteri tentang PTSL pada Badan Pertanahan Nasional Kabupaten Labuhanbatu. Jurnal Ilmiah Advokasi, 10(1), 92-97. Patoni, I., Adianto, A., dan Priyanto, A. (2022). Pengaruh Faktor Efektivitas, Efisiensi, Kecukupan, Perataan, Responsivitas, Ketepatan, terhadap Keberhasilan Pelaksanaan Pendaftaran Tanah Sistematis Lengkap (PTSL) di Kantor Pertanahan Kabupaten Indragiri Hilir Provinsi Riau. Jurnal Pendidikan dan Konseling (JPDK), 4(6), 7827-7849. Ramadhani, R. (2021). Pendaftaran Tanah sebagai Langkah untuk Mendapatkan Kepastian Hukum terhadap Hak Atas Tanah. SOSEK: Jurnal Sosial dan Ekonomi, 2(1), 31-40. Simamora, J. (2014). Tafsir Makna Negara Hukum dalam Perspektif Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. Jurnal Dinamika Hukum, 14(3), 547-561. Sukmana, O. (2016). Konsep dan Desain Negara Kesejahteraan (Welfare State). Jurnal Sospol, 2(1), 103-122. Sulistio, M. (2020). Politik Hukum Pertanahan di Indonesia. Jurnal Education and Development, 8(2), 105-105. Tan, D. (2021). Metode Penelitian Hukum: Mengupas dan Mengulas Metodologi Dalam Menyelenggarakan Penelitian Hukum. Nusantara: Jurnal Ilmu Pengetahuan Sosial, 8(8), 2463-2478.